HISTORY OF CONSCIOUSNESS - Karimov , Bozarkul Xudayberdievich (Educational Research in Universal Sciences, 2023)
The article shows that the history of consciousness is related to the history of the beginning of the formation of a person as a human being, and that consciousness has been viewed for a long time as a phenomenon within the sphere of a person, his consciousness is planetary, that is, the globe. It is stated that modern science shows the need to approach the issue in a broader framework.